Theoretical Assessment of a Hybrid Solar-Still System Via Waste Heat from Air Conditioning System Condenser - Azeez, Murtadha Hamid; Hammadi, Salman Hashim (Basrah Journal for Engineering Sciences, 2024)
In this paper, a theoretical study of the conventional solar-still system integrated via the design of heat recovery of air exhausted from the air conditioner condenser employing heat exchangers (WHRUs) was conducted. This study aims to improve desalination performance by compensating for the non-existence of sunlight during the night. A comparison was made between the desalination performance in the event of exposure to solar radiation and its performance in the case of exposure to the system (WHRUs). It was found that the (WHRUs) system has a minimal impact on the production of the conventional desalination rig during the night period, as the highest cumulative productivity in the presence of the (WHRU S ) reached (2.15 kg) in August. In contrast, the productivity dependent on solar radiation was (4.58 kg) for the same month, with the most significant percentage of improvement reaching (31.91 %).